Perception Analysis About Public Street Lighting In The Kota Kupang Nusa Tenggara Timur Province Indonesia - Jefirstson Richset Riwukore; Yohanes Susanto; Fellyanus Habaora; Hilda Manafe (PERSPEKTIF, 2021)
One of the cities in Indonesia that still performs the city arrangement is Kota Kupang in Nusa Tenggara Timur province. Several of criminal incidents and other crime allegedly occurred in areas that were still dark and there were no public street lighting. Therefore, a study has been carried out on the benefits of public street lighting in supporting population activities in Kota Kupang for six months, starting from January to June 2018. Determination sampling of respondents using purposive sampling technique. Based on this technique, then respondents in this study were 51 respondents scattered in each village at least 1 person. The data used in the research are primary and secondary data. The data obtained were then analyzed descriptively. The results of the research indicate that the implementation of public street lighting programs until 2017 has not given the Kota Kupang Government partisanship to the needs of population regarding public street lighting for daily activities.